Effect of biofertilizer (Azolla pinnata) in combination with inorganic fertilizer on growth and yield of rice - Mohamad Khair, Mohamad Izdzuan; Azman, Elisa Azura; Ismail, Roslan; Abdul Rani, Muhammad NaimFadzli (The Grassroots Institute, 2021)
This study was conducted at Malaysia Agriculture Research and Development Institute (MARDI), Seberang Perai, Penang (Malaysia), that aims to examine the impacts of the application of Azolla pinnata on the growth and performance of rice of the MR 297 variety. The experiment consisted of five treatments: PK + Azolla (T1); NP + Azolla (T2); NK + Azolla (T3); NPK-Control (T4), and Azolla only (T5). Each treatment had four replicates. The experimental design used was a complete randomized block design (RCBD), and all data collected were analyzed using one-way ANOVA with a statistically significant 0.05% test. For the average soil analysis between the beginning and end, all soil analyses showed decreased soil properties except total N and organic carbon. There is a significant effect on the tiller, panicles, yields, plant height, and SPAD value in crop growth performance. There was no significant effect on N and P among plant nutrients. In contrast, there was a significant treatment effect on K. This study concluded that the soil treated with NK + Azolla showed a comparable result with soil treated with inorganic fertilizer only for the total yield.